HIF-1 recruits NANOG as a coactivator for TERT gene transcription in hypoxic breast cancer stem cells - Lu, Haiquan; Lyu, Yajing; Tran, Linh; Lan, Jie; Xie, Yangyiran; Yang, Yongkang; Murugan, Naveena L.; Wang, Yueyang J.; Semenza, Gregg L. (Cell reports (Cambridge), 2021)
Breast cancer stem cells (BCSCs) play essential roles in tumor formation, drug resistance, relapse, and metastasis. NANOG is a protein required for stem cell self-renewal, but the mechanisms by which it performs this function are poorly understood. Here, we show that hypoxia-inducible factor 1α (HIF-1α) is required for NANOG-mediated BCSC enrichment. Mechanistically, NANOG is recruited by HIF-1 to cooperatively activate transcription of the TERT gene encoding the telomerase reverse transcriptase that maintains telomere length, which is required for stem cell self-renewal. NANOG stimulates HIF-1 transcriptional activity by recruitment of the deubiquitinase USP9X, which inhibits HIF-1α protein degradation, and by stabilizing HIF-1α interaction with the coactivator p300, which mediates histone acetylation. Our results delineate a cooperative transcriptional mechanism by which HIF-1 and NANOG mediate BCSC self-renewal. [Display omitted] •HIF-1α is required for NANOG-mediated breast cancer stem cell self-renewal•NANOG regulates TERT expression and telomere length as a HIF-1 coactivator•NANOG recruits deubiquitinase USP9X and stabilizes HIF-1α protein•NANOG stabilizes HIF-1α interaction with the coactivator p300 Lu et al. find that NANOG is necessary but not sufficient for breast cancer stem cell maintenance. NANOG functions as a HIF-1 coactivator to induce TERT expression in hypoxic breast cancer stem cells. These findings suggest a mechanism in which HIF-1 and NANOG cooperatively mediate breast cancer stem cell self-renewal.